The impact of social media on students at Binh Duong University - Ca Mau campus - Phan , Thị Ngọc Trân; Nguyen , Văn Mạnh (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This paper analyzes the negative impacts of social media on students at Binh Duong University - Ca Mau Campus, focusing on three main aspects: academic performance, mental health, and physical health. The research findings indicate that students spend a significant amount of time on social media, particularly on platforms like Facebook, TikTok, and YouTube, with more than 45% of students using social media for over six hours daily. Although social media facilitates connection and information retrieval, its excessive use has severely impacted students' concentration, resulting in sleep deprivation and impaired vision. Psychologically, students face pressure from comparing themselves to the "perfect" images portrayed online, leading to feelings of inferiority, anxiety, and isolation. Other negative effects include the lack of direct communication and neck and shoulder pain due to prolonged use of electronic devices. To mitigate these adverse effects, the paper recommends measures such as enhancing time management, promoting direct communication, and encouraging the use of social media for academic purposes more effectively. Finally, educating students on social media awareness and skills is crucial to maintaining mental and physical health and improving academic outcomes.